(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article provides a description of the establishment and spread of criminal influence as a complex form of criminal activity. It is noted that in order to implement relevant state strategies, the criminal legislation of Ukraine has been supplemented with norms aimed at neutralizing the activities of leaders of the criminal environment, as well as individual elements of the infrastructure of organized crime. The approaches to understanding the essence of «criminal activity» formed within the framework of forensic science have been analysed. Based on the positions of scientists, a distinction has been made between such categories as «crime» and «criminal activity». The existing scientific approaches to understanding the essence of criminal influence, which have been formed within the framework of criminal law and other sciences of the criminal law cycle, have been worked out. In addition, detailed attention has been paid to the set of actions that form the objective side of the establishment or spread of criminal influence through the prism of judicial practice, formed based on the results of the application of the relevant norm of criminal law. Substantiated conclusions are drawn regarding the complex of problematic issues that arise at the theoretical and applied levels during the application of the specified norms. Special attention is paid to the subject of such criminal activity, since the legislation directly links its implementation with certain characteristics of the person, in particular «authority» and «opportunity». Taking into account the study of persons who establish and spread criminal influence, typical models of gaining authority for carrying out such activity were identified. Also, the category of «opportunity» was analysed in the context of the corresponding form of criminal activity and its connection with the relevant parameters was substantiated.